Model Pengembangan Kompetensi Konselor Multikultur Berbasis Experien Learning Melalui Media Film Populer (Pawiyatan, 2015)
Asean Economic Community as a political decision sparing us not only have an impact on economic aspects alone, but also have implications for the culture. One indicator is the cross-cultural in a society that virtually no screen. Counseling as a profession affected indirectly,. Therefore, for counselors generally require the development of multicultural competence and particularly on the prospective bearers of the counseling profession. Development of multicultural counseling competencies-based experiential learning by using media popular film intended as innovative and strategic efforts to address the demands and needs.Â Â Keywords: Multicultural Counseling Competence Development. Experiential Learning, Media Popular Film